The Behavior of Maximum Outcomes in Symmetric R&D Networks - Alghamdi, Mohamad (Journal of Informatics and Mathematical Sciences, 2017)
We consider the network game for firms conduct R&D to study symmetric cooperation networks. The outcomes focus theoretically on analyzing the behavior of the equilibria. First, we determine optimal levels at which the production quantity is maximized. Then, we show that the quantity function is symmetric around those optimal levels. Finally, we show that the regular increase in the activity level does not necessarily produce a constant change in the equilibrium outcomes.